2008
DOI: 10.7326/0003-4819-149-3-200808050-00241
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: T-Cell–based Assays for the Diagnosis of Latent Tuberculosis Infection: An Update

Abstract: The IGRAs, especially QuantiFERON-TB Gold and QuantiFERON-TB Gold In-Tube, have excellent specificity that is unaffected by BCG vaccination. Tuberculin skin test specificity is high in non-BCG-vaccinated populations but low and variable in BCG-vaccinated populations. Sensitivity of IGRAs and TST is not consistent across tests and populations, but T-SPOT.TB appears to be more sensitive than both QuantiFERON tests and TST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
950
11
43

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,184 publications
(1,040 citation statements)
references
References 52 publications
36
950
11
43
Order By: Relevance
“…71,72 Unfortunately, technical and logistical challenges hinder use of TSTs, 73 and have been a barrier to scale-up of isoniazid therapy. Interferon-γ release assays that use ESAT-6 or CFP-10 antigens, or both, are an improvement on TSTs, but they are also associated with technical and fi nancial challenges, 74 and cannot yet be considered for routine use in resource-constrained settings.…”
Section: Isoniazid Preventive Therapymentioning
confidence: 99%
“…71,72 Unfortunately, technical and logistical challenges hinder use of TSTs, 73 and have been a barrier to scale-up of isoniazid therapy. Interferon-γ release assays that use ESAT-6 or CFP-10 antigens, or both, are an improvement on TSTs, but they are also associated with technical and fi nancial challenges, 74 and cannot yet be considered for routine use in resource-constrained settings.…”
Section: Isoniazid Preventive Therapymentioning
confidence: 99%
“…These one-visit, ex vivo blood tests avoid sensitization, the boosting of immune response, cross-reactivity with most nontuberculous mycobacteria, or loss to follow-up, as frequently observed with the TST (12,17). Recently, systematic reviews have shown that IGRAs have excellent specificity for the diagnosis of LTBI even in Bacillus Calmette-Guérin (BCG)-vaccinated populations (8,23). Furthermore, they correlate with occupational risk factors of TB exposure in low-incidence settings (37).…”
mentioning
confidence: 99%
“…Until recently, tuberculin skin test (TST) has been the most frequently used screening method, leading to a high rate of false positive results in M. bovis BCG-vaccinated individuals, and false negative tests in immunosuppressed persons. The new interferon gamma release assays (IGRAs) employing RD-1 antigens specific for virulent mycobacteria have excellent specificity unaffected by BCG vaccination and increased sensitivity [ 3 ]. Yet IGRAs cannot discriminate between individuals with latent and active TBI either.…”
mentioning
confidence: 99%